Evaluación de la especificidad de la prueba intradérmica de montenegro en la detección de leishmaniasis cutánea en trabajadores rurales que acuden al hospital josé maría velasco ibarra de tena durante el período diciembre 2013 - mayo 2014 - Montenegro Naranjo, Gladys Tatiana (2014)
This research aims to make the detection of cutaneous Leishmaniasis in rural workers who come to José María Velaco Ibarra Hospital in Tena, during december to may 2015. In addition, the following research is aimed at evaluation of the specificity of the intradermal test Montenegro.